Milder impact of the COVID-19 pandemic on the practice of orthopaedic surgery in Greece and Cyprus than other European countries - Kalogeropoulos, Athanasios; Savvidou, Olga D; Bissias, Christos; Sarafis, Pavlos; Savvidis, Matthaios; Tanos, Andreas; Pikoulis, Emmanouil; Papagelopoulos, Panayiotis J; Exadaktylos, Aristomenis; Eggli, Stefan (My University, 2023)
The aim of this study was to highlight the impact of the COVID-19 pandemic on the practice of orthopaedics in Greece and Cyprus.
Keywords: Arthroplasty; Coronavirus; COVID-19; Orthopaedic operations; SARS-Cov2; Trauma